2020
DOI: 10.3390/ijerph17020641
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Burnout in Midwives: A Systematic Review and Meta-Analysis

Abstract: The prevalence of burnout in midwives has been briefly studied. Given the negative effects of burnout syndrome in the physical and mental health, and also related to the quality of care provided, rates of absenteeism and sick leave; identifying related factors for the syndrome are needed. The aim was to determine the prevalence, levels, and factors related to the burnout syndrome, measured with the Copenhagen Burnout Inventory in midwives. A systematic review and meta-analysis were selected from CINAHL, LILACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 67 publications
7
94
2
7
Order By: Relevance
“…Third, healthcare providers have reported experiencing various mental health problems, including emotional exhaustion, which may result in suboptimal performance in workplaces, as found in this umbrella review. Several evidence-based reviews have reported a high burden of professional burnout among healthcare providers [44][45][46], which may exacerbate during quarantine and isolation for infection prevention. Such evidence suggests academic and professional approaches to sensitize the clinical students and healthcare providers to be aware of such issues in practical settings and adopt protective mental health measures before working in such stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Third, healthcare providers have reported experiencing various mental health problems, including emotional exhaustion, which may result in suboptimal performance in workplaces, as found in this umbrella review. Several evidence-based reviews have reported a high burden of professional burnout among healthcare providers [44][45][46], which may exacerbate during quarantine and isolation for infection prevention. Such evidence suggests academic and professional approaches to sensitize the clinical students and healthcare providers to be aware of such issues in practical settings and adopt protective mental health measures before working in such stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, this can contribute to distress and burnout, which in turn prevents midwives from being able to provide quality care and can eventually cause them to leave the profession [15]. This phenomenon does not seem to differ between settings in high -, middle-and low-income countries [16,18]. Therefore, in order to retain midwives in their work positions and enable them to provide quality care, it is crucial to create supportive work environments by ensuring su cient pre-conditions [33].…”
Section: Discussionmentioning
confidence: 99%
“…In low-and middle-income countries, such barriers have been identi ed to include economic, social, and professional areas [15][16][17]. Contributing factors include gender inequalities with a lack of power for women [15,17], low professional autonomy [14,16], and unmanageable workloads [16], the last of which is also identi ed as a signi cant barrier in high-income countries [18]. In a conceptual model on how health worker motivation is in uenced and how health sector reform can positively affect worker motivation, it has been concluded that motivating factors have a high impact on health worker performance and on general health outcomes in health workers, and that the factors cover both individual, organisational, and cultural dimensions [19].…”
Section: Introductionmentioning
confidence: 99%
“…including emotional exhaustion, which may result in suboptimal performance in workplaces, as found in this umbrella review. Several evidence-based reviews have reported a high burden of professional burnout among healthcare providers [50][51][52], which may exacerbate during quarantine and isolation for infection prevention. Such evidence suggests academic and professional approaches to sensitize the clinical students and healthcare providers to be aware of such issues in practical settings and adopt protective mental health measures before working in such stressful conditions.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%